Daya Matematis Siswa Kelas VIII dalam Memecahkan Masalah Geometri Ditinjau dari Taksonomi SOLO - Kusmaryono, Imam (Jurnal Pendidikan Sultan Agung, 2021)
Tujuan penelitian ini adalah menyelidiki adanya pencapaian KKM dari kemampuan daya matematis siswa kelas VIII dan menganalisa tingkat perkembangan kognitif dari kemampuan daya matematis siswa kelas VIII ditinjau dari Taksonomi SOLO. Penelitian menerapkan pendekatan kuantitatif. Penelitian dilaksanakan di SMP Islam Sultan Agung 4 Semarang. Populasi sebanyak 182 siswa kelas VIII. Melalui teknik cluster random sampling diperoleh kelas VIII-E (sebanyak 30 siswa) sebagai kelas eksperimen. Pembelajaran menerapkan model group investigation dengan materi geometri bangun ruang sisi datar. Instrumen penelitian meliputi soal tes tertulis.  Hasil respon jawaban siswa dari tes daya matematika dianalisa berpanduan pada Structure of the Observed Learning OutcomesTaxonomy (SOLO).  Hasil temuan penelitian menunjukkan (1)  Tingkat Perkembangan kognitif daya matematis siswa kelas VIII dalam memecahkan masalah geometri ditinjau dari taksonomi SOLO belum sepenuhnya mencapai perkembangan kognitif tingkat permikiran  kualitatif (relational dan extended abstract), tetapi masih terdapat perkembangan kognitif tingkat pemikiran kuantitatif (uni-structural dan multi-structural); dan (2) Penerapan model pembelajaran group investigation efektif dalam pencapaian KKM daya matematis siswa kelas VIII pada materi geometri.Kata kunci: Daya matematis, mathematikal power, geometri, taksonomi SOLO AbstractThe purpose of this study was to investigate the existence of the achievement of the KKM from the mathematical abilities of the eighth-grade students and to analyze the level of cognitive development of the eighth-grade students' mathematical abilities in terms of the SOLO taxonomy. This research applies a quantitative approach. The research was conducted at SMP Islam Sultan Agung 4 Semarang. The population was 182 students of class VIII. Through the cluster, random sampling technique, the VIII-E class (as many as 30 students) was obtained as the experimental class. Learning to apply the group investigation model with the geometry material of the flat side space shape. The research instrument includes written test questions. The results of student responses from the mathematics power test were analyzed based on the Structure of the Observed Learning OutcomesTaxonomy (SOLO). The results of the research findings show (1) the level of cognitive development of mathematical power of grade VIII students in solving geometry problems in terms of the SOLO taxonomy has not fully achieved cognitive development at the level of qualitative thinking (relational and extended abstract), but there is still cognitive development in the level of quantitative thinking (uni-structural). and multi-structural); and (2) The application of the group investigation learning model was effective in achieving the KKM of mathematical power of grade VIII students on geometry material.Keywords: Mathematical power, mathematical power, geometry, SOLO taxonomy